A silent gap: underrepresentation of Latin American patients in pivotal genitourinary and skin cancer trials. - Martinez-Castaneda, Erika Adriana; Overgaard, Ava Isabella De Pellegrin; Maselli-Schoueri, Jean Henri; Bell, Jennifer A H; Sridhar, Srikala S (Oncologist, 2026)
Background Latin America bears a growing burden of genitourinary (GU) and cutaneous malignancies but remains underrepresented in clinical trials that shape global standards of care. This underrepresentation raises ethical concerns and limits the generalizability of trial findings. We evaluated Latin American (LATAM) representation in pivotal GU and skin cancer trials and explored barriers to equitable inclusion. Methods We reviewed pivotal phase II and III trials in advanced GU and cutaneous malignancies (melanoma and non-melanoma skin cancers) published between 2015 and 2024. Extracted data included trial site distribution, geographic representation, and ethnicity reporting. Results A total of 46 pivotal trials (29 GU and 17 skin cancer trials), representing 38 900 patients, were included. LATAM trial sites were present in 44 studies; however, only 25 trials reported enrollment of Hispanic/Latino patients, totaling 1303 patients (3.35%). Representation across LATAM was highly concentrated in a small number of countries, including Brazil (16 trials), Argentina (14), Chile (13), Mexico (12), and Colombia (6). Participation was greater in GU trials compared with skin cancer trials. Reporting transparency was limited: Hispanic/Latino representation was reported in only 2 main publications, 5 supplementary appendices, and 23 ClinicalTrials.gov records. Conclusions Only 6.3% of participants in pivotal GU and skin cancer trials were from Latin America. Limited infrastructure, regulatory barriers, and restricted research investment likely contribute to this disparity. Improving equitable representation will require intentional trial design, stronger regional investment, and policies that move beyond nominal participation toward meaningful inclusion.